PENGARUH MEKANISME CORPORATE GOVERNANCE PADA STRUKTUR KEPEMILIKAN, FAKTOR INTERNAL, DAN FAKTOR EKSTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN (TOBIN’S Q) - Ema Radhitiya; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
The research aimed to examine the effect of corporate governance mecanism in ownership structure, intern factors, and extern factors on firm value. Intern factors are board size, and growth market. Extern factors are inflation and interest rate. This research was condusted by quantitative method and used data of industry classification listed in Indonesia Stock Exchange (IDX). The data was analyzed separately between among periods using multiple linier regression model. Total sample were 172 companies.The result of this showed research there are institutional ownership, manajerial ownership, and board size have significant effect and positive effect. Majority ownership, interest rate has positive effect but not significant. Growth market rate, interest rate, and inflation did not have significant influence to the firm value.